STATE AND DEVELOPMENT DIRECTIONS OF THE FOOD PRODUCTS MARKET OF UZBEKISTAN (Marketing Journal, 2025)
This article analyzes the current state and development trends of Uzbekistan’s food products market. The research is based on statistical data reflecting production volumes, import -export balance, price indices, and consumption indicators over recent years. The results show that although the market demonstrates stable growth, dependency on imports remains for certain product categories. The study provides practical recommendations for diversifying domestic production, modernizing logistics systems, and enhancing the competitiveness of the national food market.
Keywords: food market; production volume; import -export; competitiveness; market conditions; development trends. 210